“Diversity is a Fact, but Inclusion is a Choice”: Exploratory Open-Ended Qualitative Perspectives of Public Library Staff about the Racial Climate in the Internal Workplace of the American South - Mehra, Bharat; Black, Kimberly; Williams-Cockfield, Kaurri C.; Jaber, Baheya S. (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
This article explores open-ended qualitative feedback collected through an online survey of public library staff (e.g., managers/directors, librarians, volunteers, etc.) in the American South about the racial climate in their internal workplace. Theory of change is the conceptual principle driving this research study that calls for developing relevant solutions stemming from identifying a needed social change based on points of view of stakeholders embedded in the phenomena under study. The contextual background is the reality of racism that is THE PROBLEM in the United States and the world over. The survey questions were focused on four response categories: workplace inclusion and culture, staffing and professional development, workplace policies and procedures, and personal experiences. This research study briefly provides a listing of thematic results for each response category analyzed via application of grounded theory and open, selective, and axial coding. Implications to operationalize civic engagement for racial justice are briefly identified based on the data collected.